Direct observation of o-benzyne formation in photochemical hexadehydro-Diels–Alder (hν-HDDA) reactions. Issue 34 (19th August 2020) - Ma, Xiaonan; Maier, Jan; Wenzel, Michael; Friedrich, Alexandra; Steffen, Andreas; Marder, Todd B.; Mitrić, Roland; Brixner, Tobias
Abstract : We report the transient ultraviolet/visible absorption spectrum of an o -benzyne species in solution for the first time. Abstract : Reactive ortho -benzyne derivatives are believed to be the initial products of liquid-phase [4 + 2]-cycloadditions between a 1, 3-diyne and an alkyne via what is known as a hexadehydro-Diels–Alder (HDDA) reaction. The UV/VIS spectroscopic observation of o -benzyne derivatives and their photochemical dynamics in solution, however, have not been reported previously. Herein, we report direct UV/VIS spectroscopic evidence for the existence of an o -benzyne in solution, and establish the dynamics of its formation in a photoinduced reaction. For this purpose, we investigated a bis-diyne compound using femtosecond transient absorption spectroscopy in the ultraviolet/visible region. In the first step, we observe excited-state isomerization on a sub-10 ps time scale. For identification of the o -benzyne species formed within 50–70 ps, and the corresponding photochemical hexadehydro-Diels–Alder ( hν -HDDA) reactions, we employed two intermolecular trapping strategies. In the first case, the o -benzyne was trapped by a second bis-diyne, i.e., self-trapping. The self-trapping products were then identified in the transient absorption experiments by comparing their spectral features to those of the isolated products. In the second case, we used perylene for trapping and reconstructed the spectrum of the trapping product by removing the contribution of irrelevant species from the experimentally observed spectra. Taken together, the UV/VIS spectroscopic data provide a consistent picture for o -benzyne derivatives in solution as the products of photo-initiated HDDA reactions, and we deduce the time scales for their formation.